Iron Loss calculation in a reciprocating tubular permanent magnet motor with soft magnetic composite - Ibrahim, Taib; Wang, Jiabin; Howe, Dave (2006)
The paper describes the calculation of the iron loss in a short-stroke, single-phase, reciprocating tubular permanent magnet motor which is equipped with a soft magnetic composite (SMC) stator core and whose moving armature consists of quasi-Halbach magnetised magnet mounted on a mild steel tube, using two-dimensional time-stepped axi-symmetric finite element analysis. The iron loss is evaluated under various armature velocity profiles, on both no-load and on-load. The influence of the electrical conductivity of the SMC material on the iron loss of the tubular motor is also been investigated.